2014
DOI: 10.1208/s12249-013-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Eudragit L/HPMCAS Blend Enteric-Coated Lansoprazole Pellets: Enhanced Drug Stability and Oral Bioavailability

Abstract: Abstract. The objectives of the present work were to use blends of Eudragit L and hydroxypropyl methylcellulose acetate succinate (HPMCAS) as enteric film coatings for lansoprazole (LSP) pellets. The entericcoated pellets were prepared with a fluid-bed coater. The influence of the blend ratio, type of plasticizer, plasticizer level, coating level, and curing conditions on gastric stability in vitro drug release and drug stability was evaluated. Furthermore, the bioavailability of the blend-coated pellets in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The gastric stability and drug release of uncoated pellets were very poor, demonstrating that all of the drugs were degraded when pellets were immersed in acid medium for 10 min. Fang et al are observed that the pellets were coated with film-forming agents, and the films of coated pellets were excellent without damage in acidic medium and had better stability in neutral/alkaline medium and improved oral bioavailability of the drug [3,32,33]. The drug-loaded pellets were coated with hypromellose as a filmforming agent [20] and HPC-L as a binder or disintegrant in the powder layering process on spherical cores to fabricate round spheres and rapid dissolution [6,19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The gastric stability and drug release of uncoated pellets were very poor, demonstrating that all of the drugs were degraded when pellets were immersed in acid medium for 10 min. Fang et al are observed that the pellets were coated with film-forming agents, and the films of coated pellets were excellent without damage in acidic medium and had better stability in neutral/alkaline medium and improved oral bioavailability of the drug [3,32,33]. The drug-loaded pellets were coated with hypromellose as a filmforming agent [20] and HPC-L as a binder or disintegrant in the powder layering process on spherical cores to fabricate round spheres and rapid dissolution [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the formulations F5, F6, and F7 contain super disintegrant HPC-L which has fasten the release of drug from the formulations. An increased coating level led to an amplified extent of diffusion pathways and increasing duration of the drug to diffuse through the coating membrane [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations